(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2025)
The digital divide remains a significant challenge for ASN (civil servants, in Bahasa Indonesia abbreviation of Aparatur Sipil Negara), particularly in East Java region. This study explores the strategic implementation of the ’Webinar ASN Belajar’ program initiated by the East Java Human Resources Development Agency (BPSDM; Badan Pengembangan Sumber Daya Manusia) to enhance digital literacy among civil servants (ASN). Applying the Diffusion of Innovations Theory, the research analyzes how the webinar has been adopted across stages of knowledge, persuasion, decision, implementation, and confirmation. The research was conducted through in-depth interviews with representatives from East Java Region BPSDM to explore the program’s development, implementation, and impact. The findings reveal that the webinar improves civil servants digital skills. The study reveals that relative advantage, compatibility, and organizational support significantly influence adoption, while infrastructure limitations remain key challenges, such as limited internet access in remote areas and varying levels of digital literacy among regional civil servants. The study’s implications provide a framework for replicating similar programs in other regions and offer practical guidelines to optimize civil servants capacity development, supporting an inclusive and sustainable digital transformation in the public sector.